Hypothesis on the pathophysiology of small intestinal strangulation by a pedunculated lipoma. (8th April 2021) - Gandini, M.; Freeman, D. E.; Giusto, G.
Summary: The current hypothesis proposed for strangulation of small intestine by a pedunculated lipoma in horses involves movement of the lipoma around the small intestine until it loops through its own pedicle. This mechanism is difficult to demonstrate during surgical correction. The objective was to examine an alternative explanation for strangulation by pedunculated lipomas that is logical and consistent with intraoperative findings by the analysis of the anatomical features of 11 cases of lipoma strangulation in horses. In the proposed hypothesis, the stalk of the lipoma is tensed by the weight of the lipoma alone or by external forces on it from adjacent intestine. This produces a slit‐like aperture formed by the stalk and the contiguous mesentery. One or more loops of intestine pass across the lateral edge of the stalk before turning into this aperture, either because of lack of space in the abdominal cavity or through the effects of peristalsis. The weight of the intestine itself causes the loop to 'fall' into the aperture and become entrapped. This creates a half‐hitch knot in which the loop of intestine uses the lipoma pedicle as a 'post' around which it becomes strangulated. It was concluded that the proposed hypothesis differs from the existing one by requiring intestinal movement to create the strangulation, which is more plausible than the current proposal that the strangulation is caused by movement of the lipoma itself. It is also more consistent with surgical findings.